PENGARUH SUHU DAN KELEMBABAN UDARA TERHADAP PERUBAHAN MUTU TABLET EFFERVESCEN SARI BUAH SELAMA PENYIMPANAN [Influence of Temperature and Relative Humidity on the Quality of Fruit Juice Effervescent Tablet During Storage] - Ansar - - (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
The aim of this research was to study the influence of temperature and relative humidity on the quality of the fruit juice effervescent tablet. Sample of the passion fruit effervescent tablet was prepared from passion fruit granular, aspartame, polyetilene glycol, citric acid, and sodium bicarbonate. Variable analyzed was dissolution rate of the tablet during storage. The results indicated that temperature and humidity significantly affect dissolution rate of the fruit juice effervescent tablet. The reason for the decrease in dissolution rate was because at high storage temperature (35oC), sodium bicarbonate was not stable. The bicarbonate amount gradually decreased because it reacted with citric acid. Consequently, when the tablet was dissolved, the reaction between sodium bicarbonate and citric acid was slow. At high relative humidity (85.5%) of storage, the reaction occurred prior to the dissolution due to moisture intake.